What can we learn from the platelet lipidome?. (31st December 2023) - Chicanne, Gaëtan; Darcourt, Jean; Bertrand-Michel, Justine; Garcia, Cédric; Ribes, Agnès; Payrastre, Bernard
Abstract: Besides their proteome, platelets use, in all responses to the environmental cues, a huge and diverse family of hydrophobic and amphipathic small molecules involved in structural, metabolic and signaling functions; the lipids. Studying how platelet lipidome changes modulate platelet function is an old story constantly renewed through the impressive technical advances allowing the discovery of new lipids, functions and metabolic pathways. Technical progress in analytical lipidomic profiling by top-of-the-line approaches such as nuclear magnetic resonance and gas chromatography or liquid chromatography coupled to mass spectrometry enables either large-scale analysis of lipids or targeted lipidomics. With the support of bioinformatics tools and databases, it is now possible to investigate thousands of lipids over a concentration range of several orders of magnitude. The lipidomic landscape of platelets is considered a treasure trove, not only able to expand our knowledge of platelet biology and pathologies but also to bring diagnostic and therapeutic opportunities. The aim of this commentary article is to summarize the advances in the field and to highlight what lipidomics can tell us about platelet biology and pathophysiology. Plain Language Summary: What is the context? Lipids are a huge and diverse family of molecules strongly involved in biological membranes organization and dynamics, signal transduction, cell metabolism and intercellular communication. Earlier seminal works using conventional lipid biochemistry methods have shown the essential role of certain classes of lipids in platelet biology and platelet-related pathologies What is new? The important development of modern lipidomic analyses using mass-spectrometry now provides opportunities to investigate the entire platelet lipidome in different conditions. The application of lipidomic approaches to analyze large-scale lipid species allows platelet clinical lipidomics development. What is the impact? Study of the lipidomic landscape of platelets will expand our knowledge of platelet biology and should bring new diagnosis and therapeutic opportunities. Evaluating the functional and clinical significance of the data generated by modern platelet lipidomics appears as a vast and exciting challenge.